Infrared dielectric functions and optical phonons of wurtzite YxAl1−xN (0 ⩽ x ⩽ 0.22). (17th September 2015) - Ben Sedrine, N; Zukauskaite, A; Birch, J; Jensen, J; Hultman, L; Schöche, S; Schubert, M; Darakchieva, V
Abstract: YAlN is a new member of the group-III nitride family with potential for applications in next generation piezoelectric and light emitting devices. We report the infrared dielectric functions and optical phonons of wurtzite (0001) Y x Al1− x N epitaxial films with 0 ⩽ x ⩽ 0.22. The films are grown by magnetron sputtering epitaxy on c- plane Al2 O3 and their phonon properties are investigated using infrared spectroscopic ellipsometry and Raman scattering spectroscopy. The infrared-active E 1 (TO) and LO, and the Raman active E 2 phonons are found to exhibit one-mode behavior, which is discussed in the framework of the MREI model. The compositional dependencies of the E 1 (TO), E 2 and LO phonon frequencies, the high-frequency limit of the dielectric constant, , the static dielectric constant, , and the Born effective charge Z B are established and discussed.